Is consumption contagious? : and can it be transmitted by means of food? / by Herbert C. Clapp. - Clapp, Herbert C. (Herbert Codman), 1846- (Tufts University. Tisch Library., 2015)
Second edition.; 1 online resource (187 pages); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.